Grandmothers and Granddaughters : Old-Age Pensions and Intrahousehold Allocation in South Africa - Duflo, Esther (Washington, DC: World Bank, 2014)
This article evaluates the impact of a large cash transfer program in South Africa on children's nutritional status and investigates whether the gender of the recipient affects that impact. In the early 1990s the benefits and coverage of the South African social pension program were expanded for the black population. In 1993 the benefits were about twice the median per capita income in rural areas. More than a quarter of black South African children under age five live with a pension recipient. Estimates suggest that pensions received by women had a large impact on the anthropometric status (weight for height and height for age) of girls but little effect on that of boys. No similar effect is found for pensions received by men. This suggests that the efficiency of public transfer programs may depend on the gender of the recipient.